Computer-Controlled Local Anesthesia Complication: Surgical Retrieval of a Broken Dental Needle in Noncooperative Autistic Paediatric Patient - Damian Chybicki; Małgorzata Lipczyńska-Lewandowska; Gaja Torbicka; Anna Janas-Naze (Hindawi Limited, 2020)
The article describes an unusual case of retrieval of 8 mm fragment of a broken 30-gauge 21 mm dental needle in a 6 y.o. noncooperative autistic male patient. The needle of a computer-controlled local anesthesia device was broken during an attempt to administer local anesthetic, in order to perform conservative treatment of teeth 55 and 54 by a pedodontist. Despite the fact that the patient was under nitrous oxide sedation, an unexpected movement of the patient occurred and resulted in needle breakage. Due to the lack of patient cooperation, the surgical retrieval of a broken needle was performed under general anesthesia as part of one-day surgery procedures. The purpose of the article is to emphasize careful decision-making in proper choice of dental instruments during treatment of noncooperative paediatric patients even under sedation and to suggest dentists to carry out treatment of such patients under general anesthesia.